Answer:
y=6^x-2
Step-by-step explanation:
Start with the parent function, a^x. The graph looks like it has been translated b units down, so our function is a^x+b. Now at x=0, y=-2. So b=-2. Next at x=1, y=3. 3=a^(1)-2, a=6. y=6^x-2 is the equation
Answer:
an=6+6(n-1)
Step-by-step explanation:
<span>If the tip, t, varies directly with the number of guests, g, then it means that any change in tip there is a corresponding change in the number of guests. When the tip increases the number of guests increases as well. Therefore,
t </span>α g
To change the it to equal sign, we incorporate a proportionality constant, k.
t =<span> kg
</span>
This equation will represent the relation of t to g.
Hi there!
13y² + 10y - 3 = 5y²
Begin by moving all terms to one side:
13y² + 10y - 3 - 5y² = 0
Combine like terms:
8y² + 10y - 3 = 0
Factor using the guess-and-check method.
(4y - 1)(2y + 3) = 0
Set each factor equal to 0 to find the solutions:
4y - 1 = 0
4y = 1
y = 1/4
2y + 3 = 0
2y = -3
y = -3/2